Durkheim's Concept of Justice and its Relationship to Social Solidarity - Schoenfeld, Eugen (Sociological analysis, 1989)
Durkheim's concept of justice is defined and explored in the context of his quest for establishing a “science of moral facts.” Justice is supposed to be the basis of moral order in modern societies. Durkheim's criticisms of charity as the basis of social solidarity are explored. His Jewish background is related to his emphasis on justice as well as his scorn for charity as the basis for social solidarity. Implications for social theory are discussed briefly.